Utilização de hardware livre para implementação de controlador de bombeio centrífugo submerso aplicado em poços produtores de petróleo - Cunha, Allison Cristian da (Universidade Federal Rural do Semi-Árido, 2017)
The reduction of power consumption and operational costs in petroleum industry has become an increasingly concernment in the last years. Due to that the search for new petroleum production methods and the use of process controlling techniques integrated to its artificial lift systems for optimizing that process plays a main role, and the development of well pump controllers is the main study object. The work proposes the implementation of a control system for oil wells equipped with ESP (Electrical Submersible Pumping), having as main methodology the use of the Arduino® Platform. The desired result is the development of a low cost oil pump controller system, with software technology which brings easy configuration and remote operation, and validation of its use in a real oil well. The main goals are the cost reduction through the use of inexpensive hardware, and the the increase of developing speed by migrating to a higher level programming language, both compared to current well pumping controller solutions, based on use of PLC (Programmable Logic Controller). Other than that, the proposal represents a big step for the dissemination of open hardware philosophy for the petroleum production process control, opening doors for incoming implementation of new controllers for other artificial lift methods
Usage of open hardware for implementation of electrical submersible pump controller applied to oil wells
Keywords: Bcs; Bombeio centrífugo submerso; Elevação artificial; Controle fuzzy; Hardware livre; Esp; Electrical submersible pump; Artificial lift; Fuzzy controller; Open hardware; ENGENHARIAS::ENGENHARIA ELETRICA